View Single Post
bmannaa
bmannaa is offline
#7
Feb25-10, 10:59 AM
P: 2
Quote Quote by Mark44 View Post
Does your guess work for the given equations?
Yes it does
in the formula n^2 - 2 (n - 1) +......+ n^2 = (n-1)^3 + n^3
1) 1=1
put n = 1
2) 2 + 3 + 4 = 1 + 8
put n = 2
3) 5 + 6 + 7 + 8 + 9 = 8 + 27
put n = 3
4) 10 + 11 + 12 + 13 + 14 + 15 + 16 = 27 + 64
put n = 4
Quote Quote by Mark44 View Post
There's a lot more to this than "trivial processing." Note the title of the thread.
Yep! I didn't get to prove it by induction.